Critical project management success factors analysis for the construction industry of Bangladesh - Shuvo Dip Datta, Datta; Md. Habibur Rahman, Sobuz; Mohammad Nafe, Assafi; Norsuzailina, Mohamed Sutan; Md. Nazrul, Islam; Maria, Mannan; Abu Sayed, Mohammad Akid; Noor Md. Sadiqul, Hasan (Emerald Publishing Limited, 2023)
Purpose – This paper aims to identify the critical project management success factors and analyze those factors to achieve a sustainable construction industry in Bangladesh. Design/methodology/approach – This study identified 41 major problematic factors from the related literature. In this research, a detailed questionnaire survey was conducted among the experts and stakeholders of the construction industry of Bangladesh. The survey was carried out on a Likert scale and ranked the critical factors using the relative importance index (RII). The 41 problematic factors were divided into five group factors and ranked by the RII index to prioritize the factors. Finally, stakeholders’ opinions were analyzed with the critical assessed factors, which was a very effective technique to eliminate the risks and uncertain occurrences in the construction industry of Bangladesh. Findings – The factors analysis revealed that cost overrun, traffic jam, low wedges, slow payment for completed works and financial issues of the owner were leading critical factors in construction projects. Moreover, the critical factors are divided into five-factor groups, namely, financial management, monitoring and feedback, competency management, communication and coordination management, and risk management, which exhibit 0.767, 0.720, 0.711, 0.710 and 0.658 RII values. After all, the stakeholders’ opinion suggested that implementing modern tools and techniques can help to avoid the critical situation in the construction industry of Bangladesh. Practical implications – The construction industry of Bangladesh is moving away from stable construction work day by day. Previously, the potential CSFs were discussed unstructured way. Hence, detecting early warning signals in a structured way has become necessary for the building firm’s survival. Originality/value – Though some scattered critical issues are discussed in different literature, the critical issues of the Bangladeshi construction industry were not investigated extensively. Therefore, this study finds out the potential critical issues of the construction industry of Bangladesh to accumulate such harmful construction issues in a single platform so that the construction industry can have an overview of them with the help of innovative technologies.